Desmopressin (DDAVP) Enhances Platelet Adhesion to the Extracellular Matrix of Cultured Human Endothelial Cells through Increased Expression of Tissue Factor - Gálvez, Angel; Gómez-Ortiz, Goretti; Díaz-Ricart, Maribel; Escolar, Ginés; González-Sarmiento, Rogelio; Zurbano, María J; Ordinas, Antonio; Castillo, Ricardo (Thrombosis and Haemostasis, 1997)
The effect of desmopressin (DDAVP) on thrombogenicity, expression of tissue factor and procoagulant activity (PCA) of extracellular matrix (ECM) generated by human umbilical vein endothelial cells cultures (HUVEC), was studied under different experimental conditions. HUVEC were incubated with DDAVP (1, 5 and 30 ng/ml) and then detached from their ECM. The reactivity towards platelets of this ECM was tested in a perfusion system. Coverslips covered with DD A VP-treated ECMs were inserted in a parallel-plate chamber and exposed to normal blood anticoagulated with low molecular weight heparin (Fragmin®, 20 U/ml). Perfusions were run for 5 min at a shear rate of 800 s1. Deposition of platelets on ECMs was significantly increased with respect to control ECMs when DDAVP was used at 5 and 30 ng/ml (p <0.05 and p <0.01 respectively). The increase in platelet deposition was prevented by incubation of ECMs with an antibody against human tissue factor prior to perfusion. Immunofluorescence studies positively detected tissue factor antigen on DDAVP derived ECMs. A chromogenic assay performed under standardized conditions revealed a statistically significant increase in the procoagulant activity of the ECMs produced by ECs incubated with 30 ng/ml DDAVP (p <0.01 vs. control samples). Northern blot analysis revealed increased levels of tissue factor mRNA in extracts from ECs exposed to DDAVP. Our data indicate that DDAVP in vitro enhances platelet adhesion to the ECMs through increased expression of tissue factor. A similar increase in the expression of tissue factor might contribute to the in vivo hemostatic effect of DDAVP.